2017
DOI: 10.1101/073866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mTORC1 controls phase-separation and the biophysical properties of the cytoplasm by tuning crowding

Abstract: Summary (Abstract): (less than 150 words)Macromolecular crowding has a profound impact on reaction rates and the physical properties of the cell interior, but the mechanisms that regulate crowding are poorly understood. We developed Genetically Encoded Multimeric nanoparticles (GEMs) to dissect these mechanisms. GEMs are homomultimeric scaffolds fused to a fluorescent protein. GEMs self-assemble into bright, stable fluorescent particles of defined size and shape. By combining tracking of GEMs with genetic and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 76 publications
(81 reference statements)
4
46
0
Order By: Relevance
“…For example, the ratio of dry mass to volume defines a cell density. This quantity is related to intracellular concentrations, hence to the rates of chemical reactions occurring in the cell 1,2 . Similarly, mechanisms ensuring surfacetension homeostasis 3 can couple volume and surface area 4,5 .…”
Section: Main Text (No Heading)mentioning
confidence: 99%
“…For example, the ratio of dry mass to volume defines a cell density. This quantity is related to intracellular concentrations, hence to the rates of chemical reactions occurring in the cell 1,2 . Similarly, mechanisms ensuring surfacetension homeostasis 3 can couple volume and surface area 4,5 .…”
Section: Main Text (No Heading)mentioning
confidence: 99%
“…The large‐scale reorganization of cellular structures in quiescence is coupled with changes in the biophysical properties of the cytoplasm. Molecular crowding in the cytoplasm is highly dynamic and changes in response to stress conditions such as heat shock, osmotic stress, energy depletion, and nutrient starvation (Delarue et al, 2018; Marini, Nüske, Leng, Alberti, & Pigino, 2020; Mourão, Hakim, & Schnell, 2014; Munder et al, 2016; Riback et al, 2017). Dysregulated homeostasis of cytoplasmic crowding can contribute to cell death (Neurohr et al, 2019).…”
Section: The Cell Biology Of Quiescencementioning
confidence: 99%
“…Studies have shown that the cytoplasm of quiescent cells undergoes dramatic changes in its physical properties. Ribosome concentration appears to have important impacts on this property in a TORC1‐dependent manner (Delarue et al, 2018). Understanding the regulatory and functional connections between quiescence regulating pathways and organelle and cytoplasmic properties during quiescence presents a major challenge for future studies.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Whether such phase transitions are regulated by cells remains speculative, but it is clear that macromolecular crowding plays a key role in promoting the demixing of molecules in solution (Boeynaems et al, 2018). In the current issue of Cell , Delarue et al (Delarue et al, 2018) introduce a powerful tool for probing cytoplasmic properties at length scales previously challenging to study across a broad range of organisms, revealing that ribosome concentration regulates the diffusion of large particles and controls phase separation.…”
Section: Discussionmentioning
confidence: 99%